Revival of Geopolitics: Russian Involvement in Eastern Mediterranean (2009-2019) - ÖZSAĞLAM, MUHITTIN TOLGA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study focuses on Russian involvement in the eastern Mediterranean by referring to recent developments in the region. Certainly, the theoretical basis of the study provides geopolitical perspectives within the discipline of international relations. On the other hand, in order to consider the economic and energy problems of the region, Russia tries to establish close relations with Israel and Cyprus. Thus, Russia has pursued a proactive foreign policy in the region in the last decade and tries to maximize its participation in the region strategically to secure its national interests in both the Rimland and the Heartland. RESUMEN Este estudio se centra en la participación rusa en el Mediterráneo oriental al referirse a los desarrollos recientes en la región. Ciertamente, la base teórica del estudio proporciona perspectivas geopolíticas dentro de la disciplina de las relaciones internacionales. Por otra parte, a fin de considerar los problemas económicos y energéticos de la región, Rusia intenta establecer relaciones estrechas con Israel y Chipre. De este modo, Rusia lleva a cabo una política exterior proactiva en la región en la última década y trata de maximizar estratégicamente su participación en la región para asegurar sus intereses nacionales tanto en el Rimland como en el Heartland.